THE EFFECTIVENESS OF USING INFLUENCERS IN PROMOTING PRODUCTS IN TIKTOK SOCIAL MEDIA: A CASE STUDY ON COSMETIC BRANDS - Astita, Febriana; Andi Azhar (Pedagogic Research-Applied Literacy Journal, 2025)
This study aims to analyze the effectiveness of using influencers in promoting cosmetic products on social media. In the increasingly developing digital era, social media has become a very strategic platform for product marketing, and influencers have an important role in shaping consumer perceptions. This study uses a quantitative approach with a survey method to 200 consumers who follow influencers on the Tiktok platform, and analyzes the impact of cosmetic product promotions through content uploaded by influencers on purchasing decisions. The results of the study show that the use of influencers can increase brand awareness, build consumer trust, and encourage purchases of cosmetic products. In addition, influencer credibility factors, content relevance, and interaction with the audience have been shown to play a significant role in influencing the effectiveness of promotions. These findings are expected to provide insight for cosmetic brands in designing more effective influencer-based marketing strategies on social media.